The Relationship Between Cognitive Activation, Self-Efficacy, Achievement Emotions and (Meta)cognitive Learning Strategies Among Ugandan Biology Learners. Issue 3 (2nd September 2021) - Ekatushabe, Margaret; Nsanganwimana, Florien; Muwonge, Charles M.; Ssenyonga, Joseph
Abstract : According to the control-value theory of achievement emotions, the influence of cognitive activation teaching strategies on students' effective use of Cognitive and Meta-Cognitive (CMC) learning strategies is mediated by control appraisals (e.g. self-efficacy) and achievement emotions (i.e. enjoyment and boredom). However, there is limited and contrasting empirical evidence to support this assertion despite claims of cross-cultural and domain consistency. The present study was aimed at examining the multiple mediational roles of self-efficacy and achievement emotions on the relationship between perceived cognitive activation during instruction and four CMC learning strategies among Ugandan biology students. Data were collected using anonymous questionnaires from 587 (50.6% females) tenth grade students with a mean age of 17 years (SD = 1.16) from 10 secondary schools in Uganda. We tested the mediation hypothesis in separate models with each CMC learning strategy. Indirect effects from cognitive activation through self-efficacy and/or enjoyment to CMC learning strategies were all significant confirming their mediational roles. There were significant ( p < 0.001) direct effects from cognitive activation to: self-efficacy ( β = 0.41), enjoyment ( β = 0.26) and cognitive learning strategies, i.e. rehearsal ( β = 0.30), organisation ( β = 0.30) and elaboration ( β = 0.33). Self-efficacy and enjoyment fully mediated the relationship between cognitive activation and metacognition. Except for self-efficacy, direct effects to or from boredom were not significant. Clearly, instructional strategies in biology that stimulate thought among learners are relevant for increasing effective use of any one of CMC learning strategies.